2020
DOI: 10.1166/jctn.2020.8727
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Emergence of Digital Marketing in ASEAN Region

Abstract: To Evaluate the ASEAN countries. ASEAN’s attraction for digitalization joined with its speedy development, which means the region is home to some of the most competitive digital economies. The goal of this paper is to give methodical research on Digital Marketing in ASEAN part nations in the course of recent years. The challenge to ASEAN is to ensure that this “development gap” is well addressed. Ordinarily utilized as a wellspring of information, the Scopus database has had complete inclusion of more than 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Most ASEAN markets are actively developing based on similar scenarios as well as it is determined in the studies of scientists from USA, Malaysia and European countries (Hui 2021;Sadiq et al 2021). These scenarios are mainly determined by similar factors: the specifics of international trade, the peculiarities of long-standing sectors of the economy, as well as national traditions (Fink and Elisabetta 2019; Khan et al 2020). The ASEAN countries are characterized by the same economic features: all of them have a significant percentage of rural population, relatively low level of industrialization compared to other countries, high levels of poverty, and relatively low per capita income.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most ASEAN markets are actively developing based on similar scenarios as well as it is determined in the studies of scientists from USA, Malaysia and European countries (Hui 2021;Sadiq et al 2021). These scenarios are mainly determined by similar factors: the specifics of international trade, the peculiarities of long-standing sectors of the economy, as well as national traditions (Fink and Elisabetta 2019; Khan et al 2020). The ASEAN countries are characterized by the same economic features: all of them have a significant percentage of rural population, relatively low level of industrialization compared to other countries, high levels of poverty, and relatively low per capita income.…”
Section: Discussionmentioning
confidence: 99%
“…The study is qualitative research that compares and analyzes the information found in the studies devoted to national advertising in the ASEAN and BRICS countries. The criteria for sample were such factors as quantitative economic data, economic development data, GDP per capita, employment rate, trade balance, indicators of 1 3 international reserves, and national debt were used (Garg 2016;Boonyasana et al 2018;Khan et al 2020;Kolosova et al 2020).…”
Section: Sample and Surveymentioning
confidence: 99%
“…It becomes an indispensable tool for maintaining educational continuity and providing access to vital resources when traditional methods may be disrupted. The synergy of digital innovation and education not only enhances the learning experience but also contributes to the resilience of educational systems in the face of unforeseen challenges [38].…”
Section: Learning Sphere and Examination Methodsmentioning
confidence: 99%
“…During a pandemic, digital innovation has significant effects on social changes. Although professors and students work from home through digital education, however, with much challenges in "movement control order" by lockdown policies applied worldwide to the prevented epidemic outbreak, there is an arising digital innovation product to assist social people in safe by healthcare and overcome the difficult situation [42]. At the same time, in universities, digital innovation is leveraging the potential of collaboration and collective intelligence to design and launch more robust and sustainable entrepreneurial initiatives.…”
Section: Digital Education and Digital Innovation Development During Covid-19 Pandemicmentioning
confidence: 99%